Pleomorphic lipoma of the bulbar conjunctiva. Issue 1 (13th December 2018) - Li, Emily; Silbert, Jonathan; Sinard, John
Abstract : A 55-year-old woman presented with a painless, pink mass of the right eye bulbar conjunctiva that had been gradually increasing in size for the past 10 years. Excisional biopsy with histopathological analysis revealed a rare diagnosis of pleomorphic lipoma. There was no recurrence at last follow-up evaluation 6 months postoperatively. To the best of our knowledge, this represents the third case of pleomorphic lipoma of the bulbar conjunctiva reported to date.